2019
DOI: 10.1002/1873-3468.13521
|View full text |Cite
|
Sign up to set email alerts
|

HDAC2‐dependent miRNA signature in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) arises from a complex sequence of biological and finely orchestrated events that are still poorly understood. Increasingly, epigenetic studies are providing exciting findings that may be exploited in promising and personalized cutting‐edge therapies. A more appropriate and broader screening of possible players in cancer could identify a master molecular mechanism in AML. Here, we build on our previously published study by evaluating a histone deacetylase (HDAC)2‐mediated miRNA regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In addition, miRNAs are closely related to HDACs in different human chronic diseases and cancerogenic pathways [66]. To date, many miRNAs have been found directly targeted by HDACs in chronic metabolic diseases [67][68][69]. Intriguingly, in our study, 25 differential inflammationrelated miRNAs candidates were found by transcriptomic analysis after long-term dietary NaB supplementation.…”
Section: Plos Onementioning
confidence: 49%
“…In addition, miRNAs are closely related to HDACs in different human chronic diseases and cancerogenic pathways [66]. To date, many miRNAs have been found directly targeted by HDACs in chronic metabolic diseases [67][68][69]. Intriguingly, in our study, 25 differential inflammationrelated miRNAs candidates were found by transcriptomic analysis after long-term dietary NaB supplementation.…”
Section: Plos Onementioning
confidence: 49%
“…miRNAs are known to play a critical and functional role in a broad range of key molecular processes via sophisticated regulation of distinct targets, orchestrating a molecular intracellular balance of gene expression. Conte et al 45 identified a cluster of common upregulated and downregulated miRNAs in both SAHA-treated and HDAC2 downregulated cells in AML. Du et al 32 demonstrated that PTEN is a direct target of miR-3691-5p in HCC, and miR-3691-5p expression was elevated in both HCC tissues and cell lines, which was significantly correlated with poor prognosis and clinicopathological features.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC2 might be involved in HDAC inhibitor-medicated regulation of c-Myc. HDAC2 has a pivotal role in the modulation chromatin architecture leading to transcriptional changes (27). Previous studies reported that HDAC2 is upregulated in numerous cancer types, including breast and prostate cancer (28–30).…”
Section: Discussionmentioning
confidence: 99%